The Russian invasion of Ukraine threatens to further exacerbate the food insecurity emergency in Yemen - Kurdi, Sikandra; Breisinger, Clemens; Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
The Russia-Ukraine conflict has roiled agricultural markets, particularly the wheat market, which has seen prices rise by 30% since Russia invaded on February 24. This post focuses on the impacts of the crisis on Yemen, whose poverty, civil war, and dependence on wheat imports from Russia and Ukraine make it uniquely vulnerable to the current market and supply disruptions. Yemen’s civil war has ravaged the country since 2015, and lately serious impacts from the COVID-19 pandemic have worsened its already precarious food security situation. The prevalence of undernourishment, as measured by the UN’s Food and Agriculture Organization (FAO), exceeds 45%, and more than half of the population relies on some type of in-kind food assistance.